Physical EducatioTeachers’ Perceptions of the Importance of Physical Education for Students’ Social-Emotional Development - Wardani, Dita; Mutmainnah, Tazkiyatul; Puspita, Anis Tasya Dela; Pathurrohman, Pathurrohman (Yayasan Insan Mulia Bima, 2025)
Physical Education, Sport and Health (PJOK) plays an important role in the holistic development of elementary school students, not only from the physical aspects but also mental, social, emotional children can also learn discipline, cooperation and also maintain health from an early age. However, the implementation and prioritization of this subject is often influenced by teachers' perceptions as the main implementers in the field. This study aims to explore the views of physical education teachers regarding the importance of physical education in primary schools as well as the factors that influence their perceptions and also to find out how physical education teachers interpret the urgency of physical education in supporting the motor, cognitive and social development of primary school-age children. The research method used qualitative. Data were collected through semi-structured interviews with PJOK teachers from Plumbungan Elementary School. The results showed that the majority of PJOK teachers viewed physical education as a means to build physical fitness, motor skills, sportsmanship values, and student cooperation. However, several obstacles such as limited facilities, minimal time allocation, and lack of stakeholder support are challenges in optimizing learning. The implication of this study emphasizes the need to improve facilities, teacher training, and advocacy for the importance of PJOK in the school curriculum. This can be a reference for policy makers, schools, and teachers in strengthening physical education.